Fourier Transform Infrared Spectroscopy Study on Cation adsorption on Viscose Rayon Succinate - Khasbaatar, D; Choi, Ung Su (Mongolian Journal of Chemistry, 2014)
Ion-exchange materials have been considered as suitable material for the recovery of heavy metals in water. A viscose rayon succinate, synthesized from viscose rayon and succinic anhydride in presence of DMSO, to remove trace bivalent metal ions such as Ag+, Cu2+, Ni2+, Pb2+, Zn2+ and Cr3+, was studied using FT-IR for the behavior of metal adsorption. Both esterification and carboxyl bonding of viscose rayon succinate were assigned essentially at 1729 and 1693cm-1, respectively. And the essential band of bonding between metal and the material was determined at 1625cm-1. The available adsorption capacity of this fiber was 6.2 mequiv/g. The adsorption of metal ions on the viscose rayon succinate follows the order of Cu2+>Cr3+>Ni2+>Pb2+>Zn2+>Ag+ with maximum adsorptions capacities 4.2, 1.42, 0.91, 0.83, 0.69 and 0.35 mmol/g, respectively. DOI: http://dx.doi.org/10.5564/mjc.v12i0.189 Mongolian Journal of Chemistry Vol.12 2011: 136-141